Impact of calcium on viscoelastic properties of fortified apple tissue - Salvatori, Daniela Marisol (2011)
The objective of this study was to analyze the linear viscoelastic behavior of calcium impregnated apples by creep and sinusoidal tests and to correlate the changes in rheological parameters with some structure features. The effect of different Ca concentrations of impregnation solutions (0, 0.1 and 0.53%, w/w), system pressure (vacuum or atmospheric) and process time was studied. All samples showed a viscoelastic solid behavior with the storage modulus (G′) dominating the viscoelastic response. Treated apple samples with or without calcium showed a pronounced decrease in G′as compared with fresh tissue. Instantaneous compliance (J0), decay compliances (J1 and J2) and fluidity significantly increased after treatments, while retardation times were approximately constant. Impregnation at high calcium concentrations provoked severe folding of walls and/or a general inner disruption of cells with plasmolysis and membrane breakage in a different way according to the pressure applied and the treatment time, explaining the viscoelastic behavior. Changes in compliances and storage modulus values were significantly lower for apples treated under vacuum than when the treatment was performed at atmospheric pressure, suggesting that vacuum impregnation is an effective methodology to fortify apple tissue avoiding serious damage in viscoelastic properties and presumably in texture.